Swedish Employers and Trade Unions, Labor Migration and the Welfare State—Perspectives on Swedish Labor Migration Policy Debates during the 1960s and the 2000s - Johansson, Jesper (Nordic Journal of Working Life Studies, 2014)
This article uses a political economy approach and explores the nexus between labor migration and the welfare state and how its specificities have been viewed and presented by organized interests of employers and trade unions in Swedish labor migration policy debates during the 1960s and the 2000s. The analysis demonstrates that the Swedish Employers’ Confederation (SAF) and its organizational successor the Swedish Confederation of Enterprise (SN) have preferred a market-liberal labor migration policy. Over time, a liberal immigration policy has been viewed by employers as an important policy solution to extend levels of economic growth, increase firm competitiveness, and maintain funding for generous welfare state services. However, since the 1960s the Swedish Trade Union Confederation (LO) has preferred a state-coordinated and regulated labor migration policy. In LO’s perspective, a regulated immigration policy is a fundamental precondition for guaranteeing workers’ rights, and for minimizing potential negative effects for the functioning of the Swedish labor market model and for a prosperous Swedish welfare state.